Impact of Salicylic Acid Content and Growing Environment on Phytoprostane and Phytofuran (Stress Biomarkers) in Oryza sativa L. - Pinciroli, María (2018)
Phytoprostanes (PhytoPs) and phytofurans (PhytoFs) are oxylipins synthesized by nonenzymatic peroxidation of α-linolenic acid. These compounds are biomarkers of oxidative degradation in plant foods. In this research, the effect of environment and supplementation with salicylic acid (SA) on PhytoPs and PhytoFs was monitored by ultra-high-performance liquid chromatography coupled to electrospray ionization and triple quadrupole mass spectrometry (UHPLC-ESI-QqQ-MS/MS) on seven rice genotypes from Oryza sativa L. subsp. japonica. The plastic cover environment and spray application with 1 and 15 mM SA produced a reduction in the concentration of most of these newly established stress biomarkers [9-F1t-PhytoP, ent-16-F1t-PhytoP, ent-16- epi-16-F1t-PhytoP, 9-D1t-PhytoP, 9- epi-9-D1t-PhytoP, 16-B1-PhytoP, 9-L1-PhytoP, ent-16( RS)-9- epi-ST-Δ14-10-PhytoF, ent-9( RS)-12- epi-ST-Δ10-13-PhytoF, and ent-16( RS)-13- epi-ST-Δ14-9-PhytoF] by 60.7% on average. The modification observed in the level of PhytoPs and PhytoFs differed according to the specific oxylipins and genotype, demonstrating a close linkage between genetic features and resistance to abiotic stress, to some extent mediated by the sensitivity of plants to the plant hormone SA that participates in the physiological response of higher plants to stress. Thus, in plants exposed to stressing factors, SA contribute to modulating the redox balance, minimizing the oxidation of fatty acids and thus the syntheis of oxylipins. These results indicated that SA could be a promising tool for managing the thermotolerance of rice crop. However, it remains necessary to study the mechanism of action of PhytoPs and PhytoFs in biochemical processes related to the defense of plants and define their role as stress biomarkers through a nonenzymatic pathway.